Retroperitoneal Cyst: An Uncommon Presentation of Filariasis - Senthil Ganesan; Saurabh Galodha; Rajan Saxena (Case Reports in Surgery)
Primary retroperitoneal parasitic cysts are rare. Here we report about a middle aged male patient from rural north India with a recent onset of central abdominal retroperitoneal lump, pain, and fever. After surgical resection due to diagnostic uncertainty, at histopathology, it turned out be a filarial cyst. After receiving a course of diethylcarbamazine, the patient is asymptomatic at 4 months’ follow-up.